Sistem Informasi Infografis Berbasis Web Pada Kantor Dinas Pangan Provinsi Aceh - Pongoh, Berda Rindy; Ahmad, Lukman; Idwan, Harry (Jurnal Ilmu Komputer dan Teknologi Informasi, 2024)
This research aims to develop and implement a web-based infographic information system at the Aceh Provincial Food Service Office. This system is designed to provide easy and effective access to information about food crops through an attractive and easy to understand infographic display. The development method used is the waterfall method, which involves steps such as requirements analysis, system design, implementation, testing and evaluation. In this research, an analysis of the required data structures was carried out, such as user, commodity and production data. Next, an intuitive and responsive user interface was designed to make it easier for users to access and utilize the information presented. The testing process was carried out involving 20 respondents to test the functionality and user interface of the application. The research results show that the web-based infographic information system at the Aceh Provincial Food Service Office was successfully implemented well. This application provides benefits in accessing information related to food crops with an attractive and easy to understand display. The use of web technology in developing this application provides high flexibility and accessibility for users. The discussion of this research reveals the successful implementation of a web-based infographic information system, the benefits provided, the challenges faced, as well as recommendations for developing and improving the application in the future. It is hoped that this research can contribute to the management and decision making regarding food crops, as well as being the basis for the development of a wider web-based infographic information system